COMMUNICATION MODEL FOR TRANSFERRING LOCAL WISDOM OF GOLD BROCADE TEXTILE CHAN SOMA GROUP OF SURIN PROVINCE - SRISAPHONPHUSITTI, Thamonphat; Tokeaw , Wittayatorn; Intaratat, Kamolrat (Journal of Buddhist Anthropology, 2021)
The objectives of this research article were to study the communication pattern of local wisdom transferring on traditional royal gold brocade Chansoma Silk Weaving group in Surin Province. Qualitative methods were applied by in-depth interview, focus group discussion and observation technique. The 13 key informants were purposely selected from folk philosophers who has been experienced in weaving silk with traditional royal gold brocade over 10 years, including group administrator, group secretary, weaving managers, weavers, scholars and folk media workers. Research instruments were in-depth interview guideline, focus group discussion forms and field-note for observation which analyzed by inductive conclusion. The results revealed that 1) regarding to communication context, the community is unique in silk weaving with majority occupations are agriculture and weaving. The community’s incomes generated from selling silk which has been transferring a technique of folk weaving from generation to generation. 2) The communication process consists of the senders, namely, the villagers of the Chansoma Group, the scholars and the folk media practitioners, while the messages are the silk production process, the knowledge transferring, and the application through the channels including personal media, the product, special media and activities. The receivers include family members, academic group, folk media practitioners and general public. 3) The outstanding guideline for communication style development, namely 3 steps communication development. Firstly, the production stage by using human media through conversation, teaching, explaining, demonstrating and experimenting. Secondly, inheritance stage which focus on personal media, practice activities media by using a blended approach to oral teaching and practicality Lastly, application stage which emphasizes on the use of material products and brainstorming for the adaptation and value creation. Furthermore, the participatory communication must be used in every step.